2017
DOI: 10.1007/s12576-016-0517-5
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of ghrelin-induced feeding in rats by pretreatment with a novel dual orexin receptor antagonist

Abstract: Orexin-A and -B, and ghrelin are potent orexigenic peptides. The effects of ACT462206, a novel dual orexin receptor antagonist (DORA), on ghrelin-induced feeding were examined in adult male Wistar rats. Hyperphagia induced by the intracerebroventricular (icv) administration of ghrelin was significantly suppressed for at least 2 h by pretreatment with icv administration of DORA. A marked increase was observed in the number of neurons showing Fos immunoreactivity in the paraventricular nucleus, arcuate nucleus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 36 publications
(53 reference statements)
0
6
0
1
Order By: Relevance
“…In support of this hypothesis, GHSR is present in the LHA . Intra‐LHA administration of ghrelin increases FOS in the PVN and the administration of orexin receptor antagonists reverses the effects of ICV‐injected ghrelin on c‐FOS expression in the PVN . Interestingly, des‐acyl‐ghrelin also increases c‐FOS expression in PVN neurons after both peripheral and ICV administration, this increase, however, is less than the one achieved by ghrelin administration.…”
Section: The Pvn As a Mediator Of The Action Of Ghrelin On Energy Balmentioning
confidence: 84%
“…In support of this hypothesis, GHSR is present in the LHA . Intra‐LHA administration of ghrelin increases FOS in the PVN and the administration of orexin receptor antagonists reverses the effects of ICV‐injected ghrelin on c‐FOS expression in the PVN . Interestingly, des‐acyl‐ghrelin also increases c‐FOS expression in PVN neurons after both peripheral and ICV administration, this increase, however, is less than the one achieved by ghrelin administration.…”
Section: The Pvn As a Mediator Of The Action Of Ghrelin On Energy Balmentioning
confidence: 84%
“…Increasing evidence in clinical studies has revealed that patients with eating disorders, including food consumption, are almost entirely neglected in patients with chronic pain, which may induce a worse prognosis or a more severe pain perception 28 . Central and peripheral administration of ghrelin increases food intake dramatically in rats and mice, which may be due to activation of various brain regions, including the feeding-related areas such as the paraventricular nucleus (PVN) in rats 29,30 . So, we cannot ignore the fact the effects of ghrelin on feeding behaviour and this may alter pain sensitivity throughout the day, which will be worth a very good direction for further study in the future.…”
Section: Discussionmentioning
confidence: 99%
“…HO axons directly contact NPY and POMC neurons in the arcuate nucleus of rats and signaling through these axons has been shown to regulate their activity in a manner reciprocal to leptin ( Muroya et al, 2004 ). Moreover, ghrelin-induced food intake is significantly reduced in mice pretreated with antibodies against HO and HO knockout mice ( So et al, 2018 ). In the context of sleep deprivation, the activity of HO neurons increases to maintain wakefulness against increased pressure to sleep ( Wu et al, 2002 ).…”
Section: Sleep Disruption-induced Changes To Systemic Physiologymentioning
confidence: 99%